An abnormal triglyceride-rich lipoprotein containing excess sialylated apolipoprotein C-III. - Holdsworth, G (1982)
An abnormal triglyceride-rich lipoprotein has been isolated from some patients with chronic renal failure or severe hypertriglyceridemia. The abnormal lipoprotein was characterized by an increased content of apolipoprotein (apo) C-III-2 (57.5% of total apo C-III peptides compared with 35.5% for controls, P less than 0.001) as characterized by isoelectric focusing and scanning densitometry. As determined by a substrate competition assay, the abnormal lipoprotein was a less efficient substrate for purified bovine milk lipoprotein lipase than control lipoproteins. Neuraminidase digestion of abnormal or control lipoprotein resulted in a reduction of the apo C-III-2 band with a corresponding increase in the region of apo C-III-0, which suggests that the increased content of apo C-III-2 in the abnormal is due to excessive sialylation of the C-III peptide. Limited incubation of the abnormal lipoproteins with neuraminidase caused a partial loss of sialic acid and resulted in a triglyceride-rich lipoprotein with a normal C-III-2:C-III-1 ratio. This preparation displayed normal substrate interaction with lipoprotein lipase. Three severely hypertriglyceridemic patients with the abnormal lipoprotein showed a marked reduction in serum triglyceride concentration, which is associated with a reversion to a normal C-peptide profile after dietary therapy. The results suggest that the extent of sialylation of the apo C-III peptide carried on triglyceride-rich lipoproteins may be critical for their interaction with lipoprotein lipase.